Heterogeneous effects of eccentric training and nordic hamstring exercise on the biceps femoris fascicle length based on ultrasound assessment and extrapolation methods: A systematic review of randomised controlled trials with meta-analyses - Gokhan Yagiz (Public Library of Science (PLoS), 2021)
Objective To systematically review the effects of eccentric training based on biceps femoris fascicle length using ultrasound assessment and extrapolation methods. Design Systematic review and meta-analysis of randomised controlled trials. Data sources CENTRAL, CINAHL Plus with full text, PubMed and OpenGrey databases were searched on 6 July 2021. Eligibility criteria for selecting studies Randomised controlled trials (RCTs) lasting at least four weeks and presenting data about biceps femoris (BF) fascicle length (FL) as an outcome. Method Searching databases, screening studies, performing risk of bias assessments and determining the level of evidence (LoE) for each meta-analysis were applied during the study. PRISMA 2020 statement and Cochrane Handbook for Systematic Reviews of Interventions were used as the guidelines of this systematic review. Results Eight randomised controlled trials included in meta-analyses. Based on the very low and low LoE, eccentric training has small (g = 0.29, 95% CI [-0.26, 0.85]), moderate (g = 0.72, 95% CI [0.17, 1.28]) and large (g = 2.20, 95% CI [0.99, 3.41]) effect sizes (ES) based on manual linear extrapolation (MLE), panoramic ultrasound scanning and trigonometric equation methods, respectively. Similarly, Nordic hamstring exercise (NHE) has small (g = 0.23 [-1.02, 1.47]), small (g = 0.38, 95% CI [-0.50, 1.27]) and large (g = 1.98, 95% CI [0.52, 3.44]) ES based on the MLE, panoramic ultrasound scanning and trigonometric equation methods, respectively. Conclusion ES of eccentric training, including NHE, vary between the MLE, panoramic ultrasound scanning, and equation methods. The relevant scientific community should have a consensus on measurement standards of the BF FL measurements. Further studies can be conducted to compare the effects of eccentric training based on the ultrasound assessment and extrapolation methods.